(untitled) (Thành phố Hồ Chí Minh, 2013)
This book is designed to help you to prepare for the test in a systematic way. You will learn a lot of useful vocabulary, and you will learn how to predict and listen for different kinds of information. The exercises have been worked out for your extensive practice, and useful tips have been provided in the hope that you will be able to answer different kinds of question in the Writing test.
Keywords: English language,Ngôn ngữ Anh; Writing,Viết